2009
DOI: 10.21236/ada508422
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation and Channel Morphology Responses to Ordinary High Water Discharge Events in Arid West Stream Channels

Abstract: "Waters of the United States" (WoUS) are regulated by the U.S. Army Corps of Engineers under Section 404 of the Clean Water Act (33 U.S.C. 1344). The Corps lateral jurisdictional extent in Arid West stream channels is the upper level of the ordinary high water (OHW). The channel shape, fluvial textures, and vegetation patterns of these arid stream channels are heavily influenced by short-term, high-intensity or "flashy" events, which create distinctive physical features and vegetation responses. To determine v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The taxonomic composition and density change of woody vegetation upland of riparian areas will often be more noticeable than at the channel margin because of the steep moisture gradient. Most channels in arid regions do not have continuous flow, so the form of nonperennial channels can change dramatically between periodic small to intermediate flood events (i.e., >5 year recurrence; Lichvar et al 2009). Lichvar et al (2009) reported that flows that had less than a 5-year-recurrence interval were usually not geomorphically effective and, therefore, did not control channel form or the distribution of vegetation.…”
Section: Woody Vegetationmentioning
confidence: 99%
“…The taxonomic composition and density change of woody vegetation upland of riparian areas will often be more noticeable than at the channel margin because of the steep moisture gradient. Most channels in arid regions do not have continuous flow, so the form of nonperennial channels can change dramatically between periodic small to intermediate flood events (i.e., >5 year recurrence; Lichvar et al 2009). Lichvar et al (2009) reported that flows that had less than a 5-year-recurrence interval were usually not geomorphically effective and, therefore, did not control channel form or the distribution of vegetation.…”
Section: Woody Vegetationmentioning
confidence: 99%
“…), and sediment characteristics (e.g., composition, texture, soil development, etc. ), which in turn are driven largely by climate and geology (Lotspeich and Platts 1982;Bailey 1983;Brussock et al 1985;Omernik 1987;Snelder and Biggs 2002;Lichvar et al 2006Lichvar et al , 2009. Other variables that are potentially relevant to the occurrence and distribution of OHWM indicators include streamflow duration (i.e., perennial, intermittent, or ephemeral streamflow) and geomorphic characteristics, such as channel size and pattern (e.g., braided, single thread, etc.)…”
Section: Components Of a National Ohwm Classification Systemmentioning
confidence: 99%
“…Fluvial systems are inherently dynamic, and physical and biological field indicators of the OHWM may vary both spatially (e.g., between different regions, landscapes, and stream types) and temporally (e.g., seasonally, between flow events, and at longer time scales), thus introducing challenges to accurate and consistent delineation of the OHWM in rivers and streams throughout the U.S. Extensive research pertaining to the OHWM in non-perennial (i.e., ephemeral and intermittent) stream systems in the Arid West Region (e.g., Lichvar and Wakeley 2004;Lichvar et al, 2006;2009;Curtis et al 2011;Lefebvre et al 2013aLefebvre et al , 2013b and in the Western Mountains, Valleys, and Coast Region (e.g., has been conducted to better understand the field indicators used to identify the OHWM and to develop reliable methods for delineating the OHWM in these regions. This work has led to the development of OHWM delineation manuals for non-perennial stream systems in both regions (Lichvar and McColley 2008;.…”
Section: Introductionmentioning
confidence: 99%
“…During periods of convective monsoon season storms, high-intensity precipitation events tend to generate run-off (Snyder & Tartowski, 2006;Shaw & Cooper, 2007;Lichvar et al, 2009;Svoray & Karnieli, 2011), and strong transmission losses within the ephemeral stream channels keeps these run-off events local (Goodrich et al, 2008). Riparian vegetation along these channels maintain higher densities that can register a response to precipitation and runoff visible in satellite imagery.…”
Section: Introductionmentioning
confidence: 99%